Mapping Equity and Quality in Mathematics Education
XXXV, 624 p.
Keywords: The issues of equity and quality have been central to international debates on mathematics in research, policy, curriculum and teaching. This book covers a wide variety of topics in the research and practice of mathematics education, demonstrating how equity and quality are inherently political terms whose political bedrock is obscured by them being taken for granted. Mapping Equity and Quality in Mathematics Education is broken into four parts. Section 1 addresses the constructs of equity and quality from a variety of theoretical perspectives and outlines new directions to approach the question, “What are equity and quality?” Section 2 discusses the complexities in which the discourses of equity and quality move in constant construction and recontextualisation from societal trends to the constitution of subjectivities, passing through policy, the media and pedagogy. Section 3 covers insights and implications from research on the special needs of different “equity groups,” illuminating the way in which a “one-size-fits-all” approach tends to limit quality education to only dominant groups. And Section 4 contains lessons learned by researchers and practitioners who attempted to manage equity and quality within various educational contexts and with a variety of marginalized populations. Written by teachers, researchers and academics from all over the world, this book represents a powerful response to the international call for quality education of all students in mathematics around the globe. .